ANALISIS PENGARUH KEPERCAYAAN, PERSEPSI RISIKO, DAN E-SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN DI LAZADA DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Arin Urnika; Imroatul Khasanah (Diponegoro Journal of Management, 2023)
ABSTRACT E-commerce has created a phenomenon of shifting consumer shopping behavior from offline to online through e-commerce platforms. Lazada is one of the largest e-commerce platforms that has ever dominated the e-commerce market in Indonesia. However, along with the emergence of many e-commerce, Lazada's market share and the number of consumers visiting the Lazada website have decreased. This indicates that consumers are less willing to make purchasing decisions at Lazada. This study aims to analyze the effect of trust, risk perception and e-service quality on purchasing decisions at Lazada with purchase intention as the intervening variable. The population used is Lazada users in Indonesia. The number of samples used was 130 respondents. The data method used was a questionnaire, which was then processed and analyzed using SEM AMOS 24.0. The results of this study showed that trust has a positive and significant effect on purchase intention. Risk perception has a positive and significant effect on purchase intention. E-service quality has a positive and significant effect on purchase intention. And purchase intention has a positive and significant effect on purchasing decisions.